Pengendalian Banjir Menggunakan Pompa (Studi Kasus : Drainase Jalan Simpang Tetap Kota Dumai) - Rahmia Fauziah; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Flood is a frequent disaster in Dumai City. This study tries to solve the problem by using a pump. In order to the pump can be able to function with optimally, it is necessary to be given temporary ponds reservoirs. The pump is used to help accelerate drainage water collected in ponds. Case study area observed is Simpang Tetap street. this study conducted a simulation ponds reservoirs and pumps by water balance method. The discharge had been calculated by Rational method and IDF curve by Mononobe method. Ponds reservoirs sized (100m x 50m x 3m) requires pumping capacity of 4 m3 / sec to handle the floodwaters. So a pump 4m3 / sec can be to pump of water from ponds reservoirs to the Dumai River as channel waster.Keywords: flood, drainage system, ponds reservoirs, pumps